Tradução do instrumento Families in Early Intervention Quality of Life (FEIQOL) para a língua portuguesa do Brasil - Silva, Vitória Nigro (Universidade Federal de São Carlos, 2025)
For children with disabilities or developmental delays, early intervention plays a critical role, especially in the first years of life, marked by intense brain plasticity and rapid acquisition of skills. As theories evolved, care models shifted from child-centered approaches to perspectives that recognize the crucial role of the family and environment. In this context, instruments capable of assessing the effects of intervention on both child development and family quality of life have become increasingly relevant. The Families in Early Intervention Quality of Life (FEIQoL) questionnaire, developed by McWilliam (2021) and validated by García-Grau in Spain, addresses this need by measuring how family routines, child behavior, and overall well-being align with expectations within early intervention. This study aimed to begin the translation of the FEIQoL into Brazilian Portuguese, covering the initial stages of translation, synthesis, and back-translation. It was observed that literal equivalence does not always ensure understanding or cultural adequacy, requiring linguistic adjustments and reformulation of sentences. Given the scarcity of validated instruments in Brazil, the FEIQoL appears promising for assessing how families perceive their quality of life in relation to the supports they receive during early intervention. The initial steps were satisfactory, and advancing to the validation phase is essential to ensure practical applicability.
Translation of the instrument Families in Early Intervention Quality of Life (FEIQoL) into brazilian portuguese
Keywords: qualidade de vida; família; intervenção precoce; avaliação infantil; terapia ocupacional; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar